A state-of-the-art review of crack branching. (November 2021) - Sun, Yanan; Edwards, Michael G.; Chen, Bin; Li, Chenfeng
Abstract: Crack branching has important theoretical and practical significance in many natural phenomena and practical engineering problems. At present, the field of crack branching is still at an exploration stage, lacking a unified explanation of the underlying mechanisms and an effective method to predict crack branching in practical materials. This paper provides a state-of-the-art review of crack branching, including experimental observations, physics, fracture models and associated numerical methods. The experimental observations are first summarized, followed by the physics of crack branching. Then, the crack models including discrete crack models and smeared crack models are discussed, highlighting their key features, advantages and limitations. Next, a number of numerical methods that have been used to simulate crack branching are reviewed in detail, including the finite element method (FEM), extended finite element method (XFEM), boundary element method (BEM), meshfree methods (MMs), peridynamics (PD) and discrete element method (DEM). Finally, based on the information reviewed above, the future research directions of crack branching modelling are discussed. Highlights: This paper provides a state-of-the-art review of crack branching. It covers experimental results, causes, criteria and numerical modelling. The future research direction of crack branching modelling is discussed.